Outstanding design conditions as of 27 April, 2020 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to confirm the outstanding design conditions including kitchen style, swimming pool, AC, server room etc. for BRACU new campus project.